Sex Differences at Early Old Stage in Glycolipid Metabolism and Fatty Liver in Offspring Prenatally Exposed to Chinese Great Famine - Zhang, Yumeng; Pu, Jianhong; Ding, Yi; Wu, Lei; Yin, Yongxiang; Sun, Mingya; Gu, Ying; Zhang, Daiyi; Zhang, Ze; Zheng, Qiutong; He, Qinyuan; Xu, Ting; et al. (Frontiers in Nutrition, 2022)
Background: Chinese Great Famine (CGF) 50 years ago affected whole populations in China, its long-term influence on the offspring has attracted significant researching attention. However, information on possible metabolic differences between sexes is limited. This study explored whether there might be sex differences in risks of development of glucolipid metabolic dysfunction and fatty liver following prenatally exposure to CGF. Methods: There were 11,417 subjects around 55 years of old (6,661 males and 4,756 females). They were divided as the exposed group that fetal stage was in CGF, and unexposed group born after CGF. Analysis focused on comparisons between sexes. Results: Compared to unexposed group, the BMI and triglyceride (P<0.05) in the male were higher in exposed group, while waist circumference and blood sugar (P<0.05) in the exposed female were significantly higher. With the ages were properly balanced, the risks of glycolipid metabolic dysfunction were significantly higher in both men and women in the exposed than the unexposed (P<0.001). Prenatal exposure to CGF significantly increased risks of abnormal BMI (P<0.001, 95%CI: 2.305～2.93), blood sugar (P<0.05,95%CI: 1.050～1.401), triglycerides (P<0.05, 95%CI: 1.006～1.245), and fatty liver (P<0.001, 95%CI: 1.121～1.390) in the male, and increased risks of abnormal blood sugar (P<0.05, 95%CI: 1.024～1.689) and positive urine sugar (P<0.05, 95%CI: 1.062～6.211) in the female. Height and body weight were either the same or higher in the exposed subjects compared to the unexposed, regardless of sexes. Conclusion: This study is the first to identify sex differences in the long-term effects of CGF on metabolism and fatty liver. Importance of the findings includes that benefits precise medicine in early prevention of certain diseases for each sex before aging based on the differences revealed. This study also firstly shows “catch-up growth” in the offspring prenatally exposed to CGF as possible mechanisms underlying the long-term effects.